Human T-cell leukemia virus type II nucleotide sequences between env and the last exon of tax/rex are not required for viral replication or cellular transformation. - Green, P L (1995)
Human T-cell leukemia virus types I (HTLV-I) and II (HTLV-II) and bovine leukemia virus contain a region of approximately 600 nucleotides located 3' to the env gene and 5' to the last exon of the tax and rex regulatory genes. This region was originally termed nontranslated or untranslated (UT) since it did not appear to be expressed. Several studies have identified novel mRNAs in HTLV-I-, HTLV-II-, a bovine leukemia virus-infected cells that splice into open reading frames (ORFs) contained in the UT region and, thus, have the potential to produce proteins that might contribute to the biological properties of these viruses. The HTLV-II infectious molecular clone pH6neo has several ORFs in the UT region (nucleotides 6641 to 7213) and a large ORF which overlaps the third exon of tax/rex. To investigate the importance of these ORF-containing sequences on viral replication and transformation in cell culture, proviral clones containing deletions in UT (pH6neo delta UT) or a stop codon insertion mutation (pH6neoST) were constructed. Lymphoid cells were transfected with mutant proviral constructs, and stable cell clones, designated 729pH6neo delta UT and 729pH6neoST, were characterized. Viral protein production, reverse transcriptase activity, and the capacity to induce syncytia were indistinguishable from cells transfected with the wild-type clone. Finally, 729pH6neo delta UT- and 729pH6neoST-producer cells cocultured with primary blood T lymphocytes resulted in cellular transformation characteristic of HTLV. These results indicate that putative protein-coding sequences between env and the last exon of tax/rex are not required for viral replication or transformation in cell culture.